Environmentally benign catalysts : for clean organic reactions (Springer Netherlands, 2013)
Over the past twenty years, Catalysis by Heteropolyacids (HPAs) has received wide attention and led to new and promising developments both at academic and industrial level. In particular, heterogeneous catalysis is particularly attractive because it generally satisfies most of green chemistry's requirements. By emphasizing the development of third generation catalysts, this volume presents trends and opportunities in academic and industrial research. The book appeals to postgraduates, researchers, and chemists working in the field of environmentally benign catalysts as well as catalytic processes.